THE EFFECT OF BRAND EQUITY ON CUSTOMER SATISFACTION - Ilhamalimy, Ridho Rafqi; Sujeni, Sujeni; Krisnahadi, Tama (Dinasti Publisher, 2023)
This study aims to find out how big the influence of brand equity that consists of (brand awareness, brand association, perceived quality and brand loyalty) to customer satisfaction Oppo smartphone at STEI Rawamangun. The research method used is quantitative with quantitative decriptive approach with sample survey method, that is the technique of collecting and analyzing data by looking for opinions or opinions from the subjects studied (respondent) by using questionnaire. This research uses pursposive sampling technique that is sample determination technique with certain consideration. The sample in this research is STEI students who use Oppo smartphones. The sample used in this study as many as 100 people with the help of slovin formula. Analysis used is test of validity, reliability test and coefficient of determination.The results of partial calculations show that (1) The amount of influence of brand awareness on customer satisfaction is 9.73%, (2) The amount of influence of brand association on customer satisfaction is 4.57%, (3) The magnitude of the effect of perceived quality on customer satisfaction is 6 , 15% (4) The amount of influence of brand loyalty to customer satisfaction is 7.23. And the results of simultaneous calculations show that (5) Collectively brand awareness, brand association, perceived quality and brand loyalty have an effect on customer satisfaction is equal to 73.2%.